Food choice considerations among American Indians living in rural Oklahoma: The THRIVE study. (1st September 2018) - Wetherill, Marianna S.; Williams, Mary B.; Hartwell, Micah L.; Salvatore, Alicia L.; Jacob, Tvli; Cannady, Tamela K.; Standridge, Joy; Fox, Jill; Spiegel, Jennifer; Anderson, Natia; Jernigan, Valarie Blue Bird
Abstract: In rural American Indian (AI) communities, access to affordable, healthy foods is often limited. Understanding AI food choice considerations when selecting foods, such as sensory appeal, cost, or health, is an important yet understudied topic for eliminating persistent AI health disparities. In partnership with the Chickasaw Nation and Choctaw Nation of Oklahoma, we administered a modified version of the Food Choice Values (FCV) Questionnaire to a cross-sectional sample of 83 AI patrons shopping at tribally-owned convenience stores ≥3 times per week. The FCV Questionnaire uses 25 items to assess eight FCV subscales related to buying and eating food, including sensory appeal; safety; accessibility; convenience; health/weight control; organic; tradition; and comfort. We compared mean scores for each FCV subscale by demographic groups using t-tests and ANOVA. We used confirmatory factor analysis (CFA) to examine how well the data from this population fit FCV subscale constructs. We then used cluster analysis, MANOVA, and discriminant analysis to characterize distinct segments of the population based on patterns of FCV endorsement. Appeal, safety, and access FCVs were most strongly endorsed across the sample. Prioritization of FCVs varied by age, gender, income, and education. Our cluster analysis identified four groups, or segments, each with distinct patterns of FCV endorsement: limited endorsement of any FCVs (23.3%); safety and sensory appeal (32.9%); health/weight control (17.8%); and broad endorsement of FCVs (26.0%). These groups varied by age and employment status. Findings from this analysis informed the design and implementation of a healthy retail intervention comprised of new healthful foods and beverages, product placement and marketing strategies within four tribally-owned and operated convenience stores. Public health interventions aimed at reducing nutrition-related disparities in rural AI populations may benefit from assessing food choice considerations.